PENDIDIKAN MULTIKULTURAL DALAM MENGATISIPASI PROMBLEMATIKA SOSIAL DI ERA DIGITAL - Furhatul Fitri (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2023)
The writing of this article contains the phenomenon of education in the digital era which is growing rapidly. The use of technology in education can have a negative impact on students' social and interpersonal skills. The role of education is needed to anticipate social problems in this digital era. The writing uses the library research method by looking for related sources, in the form of articles, books, journals or other relevant sources. The article contains the cultivation of multicultural values in schools, which includes diversity education, inclusive learning, developing critical and analytical skills, good communication between people and integrating the curriculum with multicultural education. The cultivation of multicultural education in the digital age can be done through online classes and social media, Facebook, Twitter, Instagram and others, while maintaining the values of tolerance, respect for differences and recognition of cultural diversity. Keywords: Multicultural Education: Islamic Education; Digital Age